2017
DOI: 10.1038/srep41386
|View full text |Cite
|
Sign up to set email alerts
|

Systemic, Ocular and Genetic Risk Factors for Age-related Macular Degeneration and Polypoidal Choroidal Vasculopathy in Singaporeans

Abstract: To examine the association of systemic, ocular and genetic risk factors in neovascular age-related macular degeneration (nAMD) in a large cohort of Asian patients, and to further compare risk factors between those with typical AMD and polypoidal choroidal vasculoapthy (PCV) subtypes. We recruited 456 cases and 1,824 controls matched for age, gender and ethnicity. Data on systemic and ocular risk factors were collected on questionnaires. In a subgroup of subjects, we included genetic data on four AMD-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 57 publications
4
23
1
Order By: Relevance
“…It is unlikely that such an association existed in our cohort, where only one patient was diabetic. [45], but the association was not observed with either PCV or AMD in another investigation [51]. Serum total cholesterol was within normal range in all 14 patients, which may be consistent with the lack of its association with PCV reported by Fujiwara et al [52] and Li et al [54].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…It is unlikely that such an association existed in our cohort, where only one patient was diabetic. [45], but the association was not observed with either PCV or AMD in another investigation [51]. Serum total cholesterol was within normal range in all 14 patients, which may be consistent with the lack of its association with PCV reported by Fujiwara et al [52] and Li et al [54].…”
Section: Discussionsupporting
confidence: 79%
“…e Beijing Study [30] also reported a lack of such an association, contrasting with findings of a Singaporean study where smoking conferred a 4.2-fold greater risk for PVC [37]. In the Singapore Epidemiology of Eye Diseases Program [51], subjects with higher BMI were more likely to have PCV, contrasting with findings of two Japanese studies [45,52]. Because of the design of the present study, we cannot say with certainty whether higher BMI (57.1%) is a risk factor for PCV.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Interestingly Asian specific CETP D442G mutation is known to impair CETP function and increase serum high-density lipoprotein (HDL) cholesterol levels. In Asian population, higher HDL was an independent risk factor for neovascular AMD including typical AMD and PCV [62]. Similarly, genome-wide association studies conducted in Western countries have shown an association between AMD and hepatic lipase (LIPC), which also affects serum HDL cholesterol levels.…”
Section: Lipid Transportmentioning
confidence: 99%